2003
DOI: 10.1210/en.2003-0118
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Inhibits Annexin 5 Expression and Apoptosis in the Corpus Luteum of Pseudopregnant Rats: Involvement of Local Gonadotropin-Releasing Hormone

Abstract: We investigated a specific relationship between the expression of annexin 5 and prolactin in the corpus luteum of pseudopregnant rats, with particular interest in GnRH and apoptosis of luteal cells. The expression of ovarian annexin 5 mRNA was significantly decreased at mid-pseudopregnancy and recovered at the end, whereas it remained low on the corresponding day of pregnancy. The dopamine agonist CB-154, administered at mid-pseudopregnancy (d 5), increased ovarian annexin 5 mRNA, whereas prolactin, given dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 38 publications
5
34
1
Order By: Relevance
“…This protection was eliminated when prostate cancer cells overexpressed an I B superrepressor, suggesting that activation of NF B is required in the androgen survival signaling. Similarly in the corpus luteum of pregnancy we may assume that PRL, which is a survival factor according to recent evidence presented from our as well as another laboratory (Goyeneche et al 2003b, Kawaminami et al 2003, may elicit its effect by activating NF B.…”
Section: Discussionsupporting
confidence: 52%
“…This protection was eliminated when prostate cancer cells overexpressed an I B superrepressor, suggesting that activation of NF B is required in the androgen survival signaling. Similarly in the corpus luteum of pregnancy we may assume that PRL, which is a survival factor according to recent evidence presented from our as well as another laboratory (Goyeneche et al 2003b, Kawaminami et al 2003, may elicit its effect by activating NF B.…”
Section: Discussionsupporting
confidence: 52%
“…We previously reported that annexin 5 is synthesized by the gonadotropes, and that GnRH stimulates its expression [10][11][12][13]. Annexin 5 was shown to stimulate gonadotropin release leading us to propose that annexin 5 is a signal transduction factor downstream of the GnRH receptor [13,28]. The results obtained in the present study regarding the effect of annexin 5 on prolactin indicate a different mechanism of action from that seen in the gonadotropes, suggesting that annexin 5 has multiple functions in the anterior pituitary gland.…”
Section: Discussioncontrasting
confidence: 45%
“…On the other hand, GnRH may exert chronic effect in peripheral tissues since GnRH and its receptor are expressed in a wide variety of extra-pituitary tissues [32][33][34]. In fact, we recently showed that the expression of annexin A5 in the corpus luteum and also Leydig cells is stimulated by local GnRH [35,36]. Surprisingly, we found that the expression of annexin A5 mRNA was not down-regulated by continuous stimulation of GnRHa.…”
Section: Discussionmentioning
confidence: 59%